Exploring motivating factors for online pharma adoption: a systems-informed approach to design e-healthcare ecosystem - Sunita Guru; Bhavin Shah; Nishant Agrawal (Journal of Systems and Information Technology, 2026)
Purpose The technological advancements aid in improving healthcare quality and public accessibility through the adoption of online pharma (OP). However, the adoption of online pharma service (OPS) faces resistance; therefore, it is necessary to understand what motivates consumers towards its wide acceptance with enhanced technology. This study aims to investigate the critical factors and their causal relationships influencing OPS adoption within Indian context. Design/methodology/approach Fourteen motivational factors for OPS adoption have been extracted from the literature and from industry veterans. Two different multi-criteria decision-making (MCDM) methods, namely, interpretive structural modelling (ISM) and decision-making trial and evaluation laboratory (DEMATEL), have been used to examine the motivational factors for OPS adoption. In addition, common motivational factors from each method, their hierarchies and interrelationships have been established. Findings Results of ISM method revealed that lower prices (MF13), discounts or offers (MF12) and 24×7 availability (MF5) were the critical motivational factor that influenced the OPS adoption. DEMATEL method showed that confidentiality (MF1), reduced health risks (MF2) and enhanced accessibility for individuals with disabilities (MF9) were the outcome variables and revealed a high degree of dependence on fast shipping options (MF6), medicine shortage (MF8) and quality online choices (MF11). Practical implications The findings of this research will be beneficial to online pharmacy companies, pharmaceutical manufactures, logistics and supply chain partners, policy makers and regulators to devise strategies for facilitating the development of enhanced strategic approaches for inflowing or expanding OPS businesses in emerging economies. This study will also assist in designing consumer-centric health policies by understanding consumer motivational factors associated with OPS adoption, in line with the UN-SDGs #3 and #11. Originality/value An ISM–DEMATEL based hierarchical model and causal analysis for OP adoption factors, demonstrating their contextual interrelationships, has been proposed depicting a unique contribution towards understanding and facilitating the adoption of OPS in Indian context.